Entrepreneurship as a preferred career option: Modelling tourism students' entrepreneurial intention. Issue 9 (24th October 2019) - Ahmad, Noor Hazlina; Ramayah, T.; Mahmud, Imran; Musa, Mohammad; Anika, Johura Jabin
Abstract : Purpose: Building upon the theory of planned behaviour and the entrepreneurial event model, the purpose of this paper is to test the effects of the following covariates in predicting entrepreneurial intention among tourism students in Bangladesh, namely, attitude, subjective norm, perceived behavioural control (PBC), perceived desirability and perceived feasibility. Design/methodology/approach: A total of 137 private university students participated in the study by means of questionnaire. The hypotheses were tested using partial least squares (PLS) analysis. Findings: Findings indicate that attitude and subjective norm significantly influence perceived desirability. It was also found that subjective norm and PBC positively influence perceived feasibility. Interestingly also, both perceived desirability and perceived feasibility predict entrepreneurial intention. Originality/value: The study proves the robustness of the integration of the two intent models in explaining entrepreneurial intention in a developing country. The new PLS predict algorithm has been used to generate and evaluate predictions from the path model estimations.